Calixarene/azolium cyclophane hybrids: Synthesis, structure and conformations - Hesler, V.; Skelton, B.; White, A.; Brown, David; Baker, M. (Kluwer Academic Publishers, 2015)
© Springer Science+Business Media Dordrecht 2015.The synthesis, structure, and conformational behaviour of three imidazolium cyclophanes that incorporate one or two 4-tert-butylphenol or 4-tert-butylanisole groups as meta-disubstituted linkers in the macrocycle is described. The cyclophanes containing anisole moieties adopt a cone conformation in the solid state, which, in solution, is not labile on the NMR timescale. The cyclophanes containing one or two phenol moieties adopt conformations other than the cone in the solid state and are labile in solution on the NMR timescale. The phenol cyclophanes are readily deprotonated, and structural and conformational studies for a variety of the associated cyclophanes are also reported.